OHP-013 Bleeding in Cardiac Surgery: Use of Blood Coagulation Factors. (12th March 2013) - Calmels, V; Recurt-Carrere, A; Divol, E; Sallerin, B
Abstract : Background: There are few references or publications about the management of bleeding during cardiac surgery. Practices are influenced by the availability of drugs and equipment and are team-dependant. Off-label use of blood coagulation factors (BCFs) has become a major public health and financial concern. Purpose: To explain the increasing use of BCFs, during cardiac surgery under Extracorporeal Circulation (ECC), in a University Hospital setting. Materials and Methods: We assessed the amounts of BCFs and Transfused Blood Products (TBPs) used between 2009 and 2011 and compared these figures to the number of operations using ECC. Results: During this 2 years, the workload, in number of operations requiring ECC, increased by only 3% (with a decrease of 11% in emergencies). The use of TBP increased 3%. In the same time, BCF prescriptions increased dramatically (representing a cost of Euro 270, 000). The analysis of quantities dispensed shows: An increase of over 138% for Prothrombin Complex Concentrates (PCCs) Increase of over 586% for fibrinogen (Fg) Increase of over 102% for activated factor VII National figures for the same period were: 23% increase for PCC 70% increase for Fg 4% increase for FVII Conclusions: The increased use of these factors can be explained by changes in local professional practise. In order to standardise and justify the use of these costly products, multidisciplinary meetings (anaesthetists, biologists, cardiac surgeons and pharmacists) are taking place. A procedure for the management of bleeding during cardiac surgery is in development. This document should contribute to the improvement of care in terms of therapeutic efficiency and safety. No conflict of interest.